The Effect of Good Corporate Governance and Firm Size on Firm Value with Family CEO as Moderator - Silvina, Agna; Indarto, Bambang Ahmad (Research Horizon, 2026)
Generational transitions in Indonesian family businesses are analyzed via Howe and Strauss’s Generational Theory to evaluate their impact on firm value. This research aims to analyze the influence of good corporate governance mechanisms and firm size on firm value with the family CEO as a moderating variable. This quantitative study of IDX-listed family firms (2019–2024) uses purposive sampling and analyzes data with multiple linear regression and MRA. The simultaneous results indicate that independent commissioners, audit committees, board of directors, and firm size significantly influence firm value. The findings indicate that independent commissioners, audit committees, and firm size exert a positive and significant influence on family firm value, whereas the board of directors does not demonstrate a significant effect. Furthermore, the presence of a family CEO strengthens the positive relationship between independent commissioners, audit committees, and firm size and firm value, but does not moderate the relationship between the board of directors and firm value. These results imply that strengthening governance quality and aligning leadership structure are essential strategies for enhancing value creation in family firms. The findings confirm Howe and Strauss’s theory that modern leadership professionalism preserves family legacy and boosts investor confidence.